Performance of GPT-4 in Membership of the Royal College of Paediatrics and Child Health-style examination questions - Richard Armitage (BMJ Publishing Group, 2024)
The large language model (LLM) ChatGPT has been shown to have considerable utility across medicine and healthcare. This paper aims to explore the capabilities of GPT-4 (Generative Pre-trained Transformer 4) in answering Membership of the Royal College of Paediatrics and Child Health (MRCPCH) written paper-style questions. GPT-4 was subjected to four publicly available sample papers designed for those preparing to sit MRCPCH theory components. The model received no specialised training or reinforcement. The average score across all four papers was 78.1%. The model provided reasoning for its answers despite this not being required by the questions. This performance strengthens the case for incorporating LLMs into supporting roles for practising clinicians and medical education in paediatrics.